Prenusinersen economic and health-related quality of life burden of spinal muscular atrophy. (7th July 2020) - Chambers, Georgina M.; Settumba, Stella Nalukwago; Carey, Kate A.; Cairns, Anita; Menezes, Manoj P.; Ryan, Monique; Farrar, Michelle A.
Abstract : Objective: To quantify the economic and health-related quality of life (HRQoL) burden incurred by households with a child affected by spinal muscular atrophy (SMA). Methods: Hospital records, insurance claims, and detailed resource use questionnaires completed by caregivers were used to capture the direct and indirect costs to households of 40 children affected by SMA I, II, and III in Australia between 2016 and 2017. Prevalence costing methods were used and reported in 2017 US dollar (USD) purchasing power parity (PPP). The HRQoL for patients and primary caregivers was quantified with the youth version of the EQ-5D and CareQoL multiattribute utility instruments and Australian utility weights. Results: The average total annual cost of SMA per household was $143, 705 USD PPP for all SMA types (SMA I $229, 346, SMA II $150, 909, SMA III $94, 948). Direct costs accounted for 56% of total costs. The average total indirect health care costs for all SMA types were $63, 145 per annum and were highest in families affected by SMA II. Loss of income and unpaid informal care made up 24.2% and 19.8% respectively, of annual SMA costs. Three of 4 (78%) caregivers stated that they experienced financial problems because of care tasks. The loss in HRQoL of children affected by SMA and caregivers was substantial, with average caregiver and patient scores of 0.708 and 0.115, respectively (reference range 0 = death and 1 = full health). Conclusion: Our results demonstrate the substantial and far-ranging economic and quality of life burden on households and society of SMA and are essential to fully understanding the health benefits and cost-effectiveness associated with emerging disease-modifying therapies for SMA.